2014
DOI: 10.3136/fstr.20.217
|View full text |Cite
|
Sign up to set email alerts
|

Rapid Determination of Degradation of Frying Oil Using Near-Infrared Spectroscopy

Abstract: The degradation of frying oil was determined using near-infrared (NIR) spectroscopy and partial least-squares

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 20 publications
(7 citation statements)
references
References 19 publications
1
6
0
Order By: Relevance
“…It does not require additional reagents or solvents ). Previous studies have reported the determination of free fatty acid (FFA), total polar material (TPM) (Ng et al 2007;Gerde et al 2007), acid value (AV), and total polar compound (TPC) values (Yavari et al 2009;Ng et al 2011;Ogutcu et al 2012;Ma et al 2014) for heated oils with added water or other frying oil. These studies showed that the FFA and TPM values for heated edible and frying oils could be monitored using NIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…It does not require additional reagents or solvents ). Previous studies have reported the determination of free fatty acid (FFA), total polar material (TPM) (Ng et al 2007;Gerde et al 2007), acid value (AV), and total polar compound (TPC) values (Yavari et al 2009;Ng et al 2011;Ogutcu et al 2012;Ma et al 2014) for heated oils with added water or other frying oil. These studies showed that the FFA and TPM values for heated edible and frying oils could be monitored using NIR spectroscopy.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, it is extremely important to monitor the frying oil quality by considering some physicochemical parameters (Ibrahim, Abd Aziz, Hashim, Jamaludin, & Khaled, 2019; Nayak et al, 2016; Song, Kim, Kim, & Lee, 2017). The most commonly used physicochemical parameters are total polar compounds (TPC; Hammouda et al, 2019; Ibrahim et al, 2019; Li, Li, Wang, Cao, & Liu, 2017; Li et al, 2019; Ma, Zhang, Tuchiya, Miao, & Chen, 2014; Song et al, 2017), acid value (AV; Liu et al, 2019; Ma et al, 2014; Nancy, George, & Ebenezer, 2016; Nayak et al, 2016; Sayyad, 2017; Song et al, 2017), carbonyl value (CV; Shahidi Noghabi, Kaviani, & Niazmdand, 2015; Shyu, Hau, & Hwang, 1998), etc. According to Chinese Hygienic Standard (Ministry of Health of the People's Republic of China, 2004), if the AV, CV, or TPC is ≥5 mg KOH/g, 50 meq/kg, or 27%, respectively, the frying oil should be discarded.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have predicted the physicochemical parameters through regression or fitting between the physicochemical parameters and frying time, temperature, and other conditions according to the obtained data. The partial least squares regression model has been established between NIR spectra and the AV and TPC (Ma et al, 2014); thus, the AV and TPC can be predicted by observing the NIR spectra, which are measured directly from the hot frying oil. In one study (Li, Wu, Liu, Jin, & Wang, 2015), a regression model between the oil viscosity and temperature was evaluated.…”
Section: Introductionmentioning
confidence: 99%
“…19 The NIR technique has been applied in a wide range of fields in the last decades, and several of these applications are currently used for routine analyses, even in online monitoring systems. 13,20,21 It is well discussed in the literature that the water content of honey is the most important parameter for the assessment of ripeness and shelf life. In this sense, honey with a moisture content higher than 18 g/100 g can be spoiled by fermentation.…”
Section: Introductionmentioning
confidence: 99%
“…19 The NIR technique has been applied in a wide range of fields in the last decades, and several of these applications are currently used for routine analyses, even in online monitoring systems. 13,20,21…”
Section: Introductionmentioning
confidence: 99%